A Partnership Model for Improving Service Delivery in Remote Papua New Guinea: A Mixed Methods Evaluation - Emma Field; Dominica Abo; Louis Samiak; Mafu Vila; Georgina Dove; Alex Rosewell; Sally Nathan (Kerman University of Medical Sciences, 2018)
Background The Community Mine Continuation Agreement Middle (CMCA) and South Fly Health Program (the Health Program) is a partnership for improving health service delivery in remote Papua New Guinea (PNG). The Health Program is delivered by a private contractor working in partnership with existing health service providers to improve service delivery using existing government systems, where possible, and aligns with national policies, plans and strategies. A midline evaluation was conducted to determine changes in health service delivery since commencement of the Health Program. Methods A mixed methods evaluation was undertaken mid-way through implementation of the Health Program, including a pre/post analysis of health service delivery indicators, semi-structured interviews with health workers and assessment of health facility equipment and infrastructure. Results Improvements in many of the long-term expected outcomes of the Health Program were observed when compared to the pre-program period. The number of outpatient visits per person per year and number of outreach clinics per 1000 children under 5 years increased by 15% and 189% respectively (P < .001). Increases in vaccination coverage for infants aged P < .001) and 75% for 1st dose Sabin (P < .001), 30% for 3rd dose pentavalent (P < .001) and 26% for measles vaccination (P < .001). Family planning coverage remained at similar levels (increasing 5%, P = .095) and antenatal care coverage increased by 26% (P < .001). Supervised deliveries coverage declined by 32% (P < .001), a continuation of the pre-Program trend. The proportion of facilities with standard equipment items, transport and lighting increased. Health worker training, in particular obstetric training, was most commonly cited by health workers as leading to improved services. Conclusion Following implementation, substantial improvements in health service delivery indicators were observed in the Health Program area as compared with pre-program period and the stagnating or declining national performance. This model could be considered for similar contexts where existing health service providers require external assistance to provide basic health services to the community.